The Characteristics of Traditional Music Form in Palembang in Melati Karangan Song - Kautzar, Awang; Utomo, Udi (Universitas Negeri Semarang, 2018)
The purpose of this article is to discuss specifically about how the form of Malay traditional music is. It is to give insight and information about the characteristic of Malay traditional music form in Palembang. This research used qualitaive method with musicological approach. The technique of data collection are observation, interview, and documentation. The technique of data validity used triangulation. The results of the research is that there were some repetition in the main melody or vocal melody, question and response phrases, and characteristic of lyrics and the meaning of Malay traditional song in Palembang. One of traditional song in Palembang is Melati Karangan, this song is a symbol or an identity of Palembang that always respects a woman or older people. The musical performance in Melati Karangan song is usually presented in wedding traditional ceremony. The tribute to women, parents and guests in Palembang representing courtesy in the marriage process, is part of Malay cultural identity in Palembang.